2014
DOI: 10.4103/0331-3131.141025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a behavioral intervention on male involvement in birth preparedness in a rural community in Northern Nigerian

Abstract: A B S T R A C TIntroduction: Delays in care seeking for obstetric emergencies are major determinants of maternal death in Nigeria. Birth preparedness has been found to be effective in reducing these delays. Male involvement is necessary for improving birth preparedness because of patriarchy which allows men to control women's access to and utilization of maternal health care. Aim: To assess the effect of a health promotion intervention on male involvement in birth preparedness in a rural community in northern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 10 publications
2
13
3
Order By: Relevance
“…Similarly, a study in Indonesia found that men had increased knowledge and participation in birth preparations and delivery care after being exposed to a multimedia entertainmenteducation intervention programme on birth preparedness [18]. The high increase (73%) in spousal participation in birth preparedness after the intervention noted in this study, is different with the 21% reported in another intervention study done in Nepal [15] and 6.2% in Northern Nigeria [19]. The possible explanation for these differences is that the baseline level of birth preparedness found in this study was higher than both of the studies it is being compared with.…”
Section: Interpretation Of Resultscontrasting
confidence: 85%
“…Similarly, a study in Indonesia found that men had increased knowledge and participation in birth preparations and delivery care after being exposed to a multimedia entertainmenteducation intervention programme on birth preparedness [18]. The high increase (73%) in spousal participation in birth preparedness after the intervention noted in this study, is different with the 21% reported in another intervention study done in Nepal [15] and 6.2% in Northern Nigeria [19]. The possible explanation for these differences is that the baseline level of birth preparedness found in this study was higher than both of the studies it is being compared with.…”
Section: Interpretation Of Resultscontrasting
confidence: 85%
“…Lack of husband participation in birth preparedness plans and delays in care seeking for obstetric emergencies are main contributing factor of maternal death. Male involvement is essential for improving birth preparedness because of patriarchy which agree to men to control women's access to and utilization of maternal health care and safe motherhood programs which may be affected by male partner participation because husbands were the most influential decision-maker and as the key member of the family [13].…”
Section: Introductionmentioning
confidence: 99%
“…Although adding name of a baby to the existing content on BP/CR would be good practice, this should be done with caution. Birth preparedness and complication readiness aim at reducing delays which contribute to poor access to maternal health services among women, ultimately reducing maternal mortality26,27. Adding the baby's name to the strategy may not assist in achieving the purpose of the strategy.…”
Section: Discussionmentioning
confidence: 99%